Corneal Reinnervation and Sensitivity Recovery after Pterygium Excision. (22nd February 2020) - Zhao, ZhanLin; Zhang, JiaYing; Liang, Hong; Zhang, SiYi; Shao, ChunYi; Fan, XianQun; Fu, Yao
Abstract : Purpose . To evaluate changes in corneal sensitivity and subbasal nerve density after pterygium excision. Methods . This prospective trial included 22 eyes with nasal primary pterygium and 18 controls. Corneal sensitivity was evaluated using a Cochet–Bonnet esthesiometer in the nasal, superior, temporal, inferior, and center quadrants of the cornea before surgery and 10 days, 1 month, and 3months after surgery. The central cornea was analyzed using in vivo confocal microscopy (IVCM) before surgery and 1 and 3 months after surgery. Subbasal nerve density and other nerve parameters were analyzed using NeuronJ. Nerve tortuosity was evaluated and graded in individual IVCM scans. The tear film break-up time (TBUT) test and Schirmer's test were performed before surgery, as well as 1 and 3 months after surgery. All the same tests were performed in the controls. Results . All affected eyes showed a significant increase in corneal sensitivity in the nasal corneal quadrant after surgery when compared with preoperative data ( F = 37.3; P < 0.01 ). Compared with controls, pterygium patients demonstrated decreased corneal subbasal nerve density (P < 0.01 ), fewer nerve trunks (P < 0.01 ), and fewer nerve branches (P < 0.05 ). However, an increased central corneal subbasal nerve density was observed 1 month after surgery compared with preoperative data, after which the density became stable ( F = 9.62; P < 0.01 ). Nerve tortuosity showed no difference between the two groups or across different time points in patients. Similarly, patients with pterygium demonstrated a decrease in TBUT (P < 0.01 ) when compared with controls. A tendency toward increase was observed in the TBUT test after pterygium excision ( F = 2.873; P = 0.07 ). However, no difference was observed in Schirmer's test. Conclusion . Pterygium patients demonstrated deteriorated corneal subbasal nerve fibers when compared with healthy controls in terms of nerve length, nerve trunks, and nerve branches. Therefore, pterygium excision improves corneal sensitivity and increases corneal subbasal nerve density.